Menapak jalan berliku : sebuah otobiografi - Soejoeti, Zarkowi (Jakarta : DPP GUPPI, 2010)
Autobiography of Zarkowi Soejoeti, a former Indonesian ambassador to Saudi Arabia and Syria.
INludes index.
Keywords: Soejoeti, Zarkowi, -- 1934-.; Ambassadors -- Indonesia -- Biography; Diplomats -- Indonesia -- Biography